Методи та засоби контролю навколишнього природного середовища - Люліна, К. П. (ХНУРЕ, 2019)
The given work is dedicated to the methods of environment controlling. Today technologies is developing progressively and people influence the nature more and more. During last 100 years the quality of environment dramatically changed, that is the reason why it is important to control processes occurring in the nature as a result of human being.